Greetings to Liv Merete Nielsen - Berg, Arild (FormAkademisk, 2023)
Liv Merete Nielsen has meant a lot to me in my development as a researcher and person. She has shown how she can be a personal and friendly person just being herself, while at the same time entering large international research arenas with the greatest naturalness. She has shown in an exemplary way how to build a new research field within the design profession in Norway where you combine professional expertise at an international level with interpersonal relationships. She has impressed me in taking an appropriate number of initiatives, but not too many, which she has then followed up with systematic, gentle and friendly, iron will. There has never been an unkind word, but through pleasant and enthusiastic appeals, everlasting, she has engaged, gathered, and uplifted an entire professional environment. This has happened across institutions, across departments and across national borders.